2013
DOI: 10.1186/1476-4598-12-115
|View full text |Cite
|
Sign up to set email alerts
|

CD164 regulates the tumorigenesis of ovarian surface epithelial cells through the SDF-1α/CXCR4 axis

Abstract: BackgroundCD164 (endolyn), a sialomucin, has been reported to play a role in the proliferation, adhesion, and differentiation of hematopoietic stem cells. The potential association of CD164 with tumorigenicity remains unclear.MethodsThe clinicopathological correlation of ovarian cancer with CD164 was assessed in a 97-patient tumor tissue microarray. Overexpression or silence CD164 was to analyze the effect of CD164 on the proliferation, colony formation and apoptosis via a mouse xenograft and western blotting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 47 publications
(60 reference statements)
2
39
0
Order By: Relevance
“…In lung cancer, the positive associations were significantly existed between CD164 expression and tumor size, tumor cell grading, and lymph node involvement 14. Besides, a high abundance of CD164 protein was significantly correlated with high‐grade of ovarian tumors 15. In our study, the results of immunohistochemistry from 115 patients showed that high expression of CD164 was associated with clinical‐pathological characters such as distant metastasis and vascular invasion.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…In lung cancer, the positive associations were significantly existed between CD164 expression and tumor size, tumor cell grading, and lymph node involvement 14. Besides, a high abundance of CD164 protein was significantly correlated with high‐grade of ovarian tumors 15. In our study, the results of immunohistochemistry from 115 patients showed that high expression of CD164 was associated with clinical‐pathological characters such as distant metastasis and vascular invasion.…”
Section: Discussionsupporting
confidence: 54%
“…As CD164 acted as a CXCR4‐associated sialomucin, the relationship between CD164 and CXCR4 has been researched in many different cancers 15, 23. In our study, we used the immunohistochemistry to observe the association between the expression of CD164 and CXCR4 in tumor tissues by uninterrupted slicing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In prostate cancer, CD164 was found to promote metastasis through the chemokine receptor type 4 (CXCR4) / stromal cell-derived factor-1 (SDF-1) interaction (Havens et al, 2006). A recent study showed that CD164 promoted tumourigenicity through the CXCR4/SDF-1 α axis in an in vivo ovarian cancer model (Huang et al, 2013).…”
mentioning
confidence: 99%